ELEMENTS OF TECHNOLOGY OF FORMATION OF STUDENTS’ PROFESSIONAL AND VALUE ORIENTATIONS - Morin, Oleh (Theoretical and Methodical Problems of Children and Youth Education, 2022)
Person’s professional self-determination has decisive consequences not only for the future life of an individual, but affects society in general. By choosing a profession, a person not only takes the first steps on the way to building a professional career, but also develops the professional values based on which he or she will contribute to the development and improvement of a certain professional field in the future. That is why the study of the problem of the formation of students’ professional and value orientations, and especially the implementation of pedagogical technology to ensure the specified process, has become relevant. The article briefly reveals the features of using the method of projects and career guidance games as important elements of the procedural and practical component of the technology of the formation of students' professional and value orientations. It is noted that during the implementation of the projects there is an indirect promotion of the emergence of personal experiences among students, a selective attitude towards a certain professional activity, which, as a result, determines changes in life activities, the construction of a conditional trajectory of movement in the acquisition of a certain professional education. The career guidance game in a non-obtrusive way promotes students' assimilation of career guidance knowledge, provides students with the world of work and professions, understanding of facts, processes, acquisition of certain abilities, skills, methods of practical activity, promotes the development of students’ abilities to apply the acquired knowledge in practice, promotes professional self-determination. It is noted that the study of the problem of the formation of students’ professional value orientations made it possible to establish the main factors affecting the effectiveness of the specified process, in particular, to identify the potential for increasing its effectiveness through using traditional forms and methods, for example, the method of projects and career orientation games.